Arsenic trioxide exposure impairs testicular morphology in adult male mice and consequent fetus viability - da Silva, Raquel Frenedoso; Borges, Cibele dos Santos [UNESP]; Lamas, Celina de Almeida; Cagnon, Valéria Helena Alves; Kempinas, Wilma de Grava [UNESP] (Taylor & Francis, 2017)
The acute promyelocytic leukemia (APL) is a rare disease, affecting 0.1/100,000 individuals globally. Despite significant advances in APL therapy, some patients still experience relapsed disease. Currently, arsenic trioxide (As2O3) was found to be effective in relapsed APL treatment and considered as standard treatment for these cases. However, it has been shown that exposure to As2O3 may exert adverse effects on the male reproductive system since this substance might also induce apoptosis of other important cell types including stem cells. Studies demonstrated that treatment with this metallic substance decreased plasma levels of testosterone and interfered with sperm parameters such as concentration, motility, and viability. In addition, As2O3 was found to produce significant damage to spermatocytes, which may be associated with testicular toxicity and consequent inhibition of spermatogenesis. The aim of this study was to determine subchronic treatment effects of As2O3 on sperm and testicular morphology, androgen receptor (AR) immunoreactivity in testes and epididymis, in addition to evaluation of fertility parameters in adult male mice. Thirty adult Swiss mice were divided into three experimental groups: control; received distilled water (vehicle) while treated received 0.3 or 3 mg/kg/day As2O3 subcutaneously, for 5 days per week, followed by 2 days of interruption, for 5 weeks. Results showed that As2O3 (1) decreased spermatozoa number, (2) produced seminiferous epithelium degeneration and exfoliation of germ cells tubule lumen (3) altered nucleus/cytoplasm proportion of Leydig cells and (4) reduced AR immunoreactivity in both Leydig and epithelial epididymal cells. Further, fetal viability tests demonstrated an increase in post-implantation loss in females that were mated with As2O3- treated males. Data indicate that As2O3 exposure altered the spermatogenic process and subsequently fetal viability.
Keywords: Androgen receptor; Arsenic trioxide; Post-implantation loss; Sperm malformation; Toxicology